Research, development and transfer of environmentally sound technologies in Brazil - Jeovan de Carvalho Figueiredo; Luiz Carlos Di Serio; Jislaine de Fátima Guilhermino; Wladimir Augusto César de Morais; Vera Lucia Neto (Innovation & Management Review, 2019)
Purpose: Most research and development (R&D) activities in Brazil are performed by science and technology institutions (STIs). The purpose of this research was to determine whether environmentally sound technologies (ESTs) developed by these organizations were transferred to companies, either through cooperation during research or through mechanisms such as licensing agreements or spin-offs. Design/methodology/approach: In total, 1,939 research groups and 702 patent registers, identified from the same set of words related to ESTs, using semantic search in open-access databases, covering a period from 2005 to 2014, were examined. The two data sets (patents and research groups) were overlaid, and it was possible to associate inventors' names with researchers' names. Findings: The results showed that only six patents could be related to the 1,939 identified research groups. Of the six patents, only one was the object of a licensing agreement, and no spin-off was identified. Practical implications: This study evidenced that it is necessary to expand the mechanisms of knowledge transfer, directed not only from STIs to companies but also in the opposite direction, given that companies recognize potential market opportunities. Originality/value: This study shows that improvements in the Brazilian National Innovation System are necessary, as ESTs research groups demonstrated a weak association with technologies transferred to companies, with only one case of technology transfer in the form of a licensing agreement.
Keywords: 650; Technology transfer; Spin-offs; Patent; Public research organizations; Science and technology institutions (STIs)